On the evolution of profiles and fluctuations towards the L-mode density limit in ASDEX Upgrade - G. Grenfell; M. Griener; M. Bernert; J. Adamek; D. Brida; M. Faitsch; P. Manz; B.Ph. van Milligen; U. Stroth; the ASDEX Upgrade Team; the EUROfusion Tokamak Exploitation Team (Nuclear Fusion)
The maximum achievable density in a tokamak is restricted by the so-called density limit. In this contribution, we observe that a MARFE precedes the final chain of events leading to disruption in ramp up L-mode discharges, resulting in strong power dissipation and plasma cooling, which likely makes the plasma unstable to MHD modes. However, this phase is preceded by an initial cooling governed by enhanced radial transport due to higher fluctuations and a more favorable cross-phase for transport, which likely impacts the MARFE formation. The increase in radial turbulent transport near the separatrix is primarily observed following the detachment of the outer divertor. This occurs when an X-point radiator forms and the edge collisionality rises, indicating that the increased collisionality influences the turbulence characteristics in the plasma boundary. The causal connection between the events that precede the disruption is discussed.